Relationships Among Dietary Cognitive Restraint, Food Preferences, and Reaction Times - Masterson, Travis D.; Brand, John; Lowe, Michael R.; Metcalf, Stephen A.; Eisenberg, Ian W.; Emond, Jennifer A.; Gilbert-Diamond, Diane; Marsch, Lisa A. (Frontiers in Psychology, 2019)
Objective: To assess the associations between dietary cognitive restraint, disinhibited eating, and how taste and health perceptions relate to food preference; and further, whether cognitive restraint and disinhibited eating are associated with food preference decision reaction time. Methods: Five hundred and seventeen adults participated in the study. Dietary cognitive restraint and disinhibited eating were assessed using the shortened Three-Factor Eating Questionnaire (TFEQ-R18). Participants also completed a dietary decision-making task to examine their food-related decisions. Participants were presented with 50 food items and asked to rate them for health and for taste. Participants were then presented with a reference food item and comparison items one at a time and asked to indicate which of the two foods they would prefer to eat. Results: Participants with higher levels of cognitive restraint were more sensitive to health perceptions whereas those with higher levels of disinhibited eating were more sensitive to taste perceptions when indicating food preference. Reaction time analysis corroborated these results. Being classified as high for cognitive restraint was associated with faster reaction times if the preferred food was rated as healthier than the referent food. Conversely, being classified as high for disinhibited eating was associated with faster reaction times if the preferred food was rated as tastier than the referent food. Conclusions: The dietary decision-making task appears to capture distinct aspects of dietary restraint and disinhibition and may be useful in future studies to measure and/or alter levels of dietary restraint and disinhibition.